2020
DOI: 10.1002/bse.2689
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of a sustainable innovation system

Abstract: This study seeks to identify and define the determinants of the sustainable innovation system (SIS). To achieve the objective, a qualitative approach was used through a systematic literature review using data from Web of Science (WOS) and Scopus. Two search equations were used to extract the data. In the first search equation, 69 documents were analyzed, and for the second, 102 documents were analyzed. Multiple definitions were found regarding SIS, it is worth highlighting in the findings the evolutionary proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…However, the weak presence of networking ties slows EIs and thus the competitiveness of SMEs. The mentioned intermediaries might help SMEs establish those connections with other enterprises indispensable to obtained steady orders, acquire know‐how, and enter into foreign markets, thus enforcing their competitiveness and triggering EIs (Zartha Sossa et al, 2020; Zubeltzu‐Jaka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the weak presence of networking ties slows EIs and thus the competitiveness of SMEs. The mentioned intermediaries might help SMEs establish those connections with other enterprises indispensable to obtained steady orders, acquire know‐how, and enter into foreign markets, thus enforcing their competitiveness and triggering EIs (Zartha Sossa et al, 2020; Zubeltzu‐Jaka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, literature reviews of SMEs have found from 35 (Díaz-García et al, 2015) up to 79 determinants (Zartha Sossa et al, 2020).…”
Section: Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…But how fast should a company shift to offering more products with a higher sustainability performance? A company might have products with low sustainability performance that generate high revenue in the short term, but in the long term, these products can be rejected due to environmental legislation or changing customer requirements (Zartha Sossa et al, 2020). At the same time, the company may develop products with a higher sustainability performance that are not profitable in the short term, but in the future, these products might have a higher revenue, complying with new environmental regulations and being ahead in the market (Schulte et al, 2020).…”
Section: Introductionmentioning
confidence: 99%